Digital Teaching Reinvented: The Effectiveness of AI-Based and IFP-Based Interactive Media in Improving Teacher Competence - Brezto Asagi Dewantara; Eka Cahya Sari Putra; Fitri Nurmahmudah (Pedagogik Journal of Islamic Elementary School, 2025)
Digital transformation in education requires teachers to have competencies that are not only technically strong, but also adaptive and creative in utilizing smart technologies. This study aims to analyze the effectiveness of "Digital Teaching Reinvented" training that integrates the use of Artificial Intelligence (AI) and Interactive Flat Panel (IFP)-based media in improving teachers' digital competence. The research design used a one-group pre-post test involving 32 teachers who participated in intensive training based on direct practice and media co-creation. Data was collected through competency evaluation instruments covering three main domains: AI-based media competence, IFP media competency and attitudes, and overall digital competence. Data analysis was carried out using a paired sample t-test, Wilcoxon test, and effect size calculation. The results of the study showed a significant increase in all competency domains. AI-based media competence increased from an average of 43.81 to 63.56 (p < 0.001; d = 1.50), IFP media competence and attitudes increased from 110.00 to 173.44 (p < 0.001; d = 2.16), while total digital competence increased from 76.91 to 118.50 (p < 0.001; d = 2.03). This improvement confirms that training that combines AI media design and IFP operation is able to strengthen technical skills, pedagogical readiness, and teachers' attitudes towards learning technology. These findings also show that integrative training models can accelerate teachers' ability to design innovative, interactive, and student-centered learning. This research provides theoretical and practical contributions through empirical evidence that AI–IFP integration-based training can be an effective strategy to improve teachers' digital competencies in the era of smart learning. This training model is recommended as an approach that can be replicated in various educational contexts to strengthen teachers' readiness to face the challenges of sustainable digital transformation.